Pendidikan Islam dalam Tantangan Era Globalisasi - Imam Tabroni; N. Nia Herawati ‎; Wildan Pitriawan ‎; Sukron Amin ‎ (Indra institute Research & Publication, 2022)
This discussion aims to analyze the role of islamic education in facing the challenges of the current era of globalization. This discussion in focused on what is the era of globalization? What is the effect of globalization on islamic education today? And how is islamic education in the face of challenges in globalization? The data is obtained through library sources which are then analyzed for their relevance to the fact that are happening at this time. And the challenges faced by Islamic education are modernization and technological advances, so that Islamic education is required to be able to adapt to current conditions in order to compete in facing today's global challenges.